FEATURES OF KIDNEY DAMAGE IN CHILDREN WITH OBESITY - Garifulina Lilya Maratovna; Goyibova Nargiza Salimovna; Ashurova Maksuda Zhamshedovna (Galaxy International Interdisciplinary Research Journal, 2022)
The review provides information about the morphology and function of the kidneys in children with obesity. The influence and interrelationship of numerous pathogenetic factors affecting the functioning of the kidney is discussed. The use of early biomarkers of kidney pathology in obesity with an assessment of the level of lipid and carbohydrate metabolism, insulin resistance, serum leptin and adiponectin is promising for diagnosing renal lesions in obesity in children.